2008
DOI: 10.1016/j.bmc.2008.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Total syntheses of (±)-ovalicin, C4(S∗)-isomer, and its C5-analogs and anti-trypanosomal activities

Abstract: Total syntheses of (±)-ovalicin, its C4(S*)-isomer 44, and C5-side chain intermediate 46 were accomplished via an intramolecular Heck reaction of (Z)-3-(t-butyldimethylsilyloxy)-1-iodo-1,6-heptadiene and a catalytic amount of palladium acetate. Subsequent epoxidation, dihydroxylation, methylation and oxidation led to (3S*,5R*,6R*)-5-methoxy-6-(t-butyldimethylsilyloxy)-1-oxaspiro [2.5]octan-4-one (2), a reported intermediate. The addition of a side chain with cis-1-lithio-1,5-dimethyl-1,4-hexadiene (27) followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…[59] Primary and secondary amines, however, require temporary blocking by protonation with trifluoroacetic acid to prevent side reactions (Scheme 8). [57] Moreover, the oxidation of alcohols by IBX tolerates a wide variety of other functional groups such as allenes, [60] azides, [61] cyclopropanes, [62] diazo compounds, [63] epoxides, [64,65] phosphates, [66] phosphonates, [67] silanes, [68] germanes, [69] stannanes, [70] trifluoroborates, [71] iron and rhenium complexes, [72,73] as well as a large number of nitrogen-and sulfur-containing heterocycles. [74][75][76][77][78][79][80][81][82][83][84] Furthermore, most commonly employed protecting groups are compatible with IBX, the use of which in organic synthesis is steadily increasing as a result of these advantages.…”
Section: Simple Oxidation Of Alcohols and Diolsmentioning
confidence: 99%
“…[59] Primary and secondary amines, however, require temporary blocking by protonation with trifluoroacetic acid to prevent side reactions (Scheme 8). [57] Moreover, the oxidation of alcohols by IBX tolerates a wide variety of other functional groups such as allenes, [60] azides, [61] cyclopropanes, [62] diazo compounds, [63] epoxides, [64,65] phosphates, [66] phosphonates, [67] silanes, [68] germanes, [69] stannanes, [70] trifluoroborates, [71] iron and rhenium complexes, [72,73] as well as a large number of nitrogen-and sulfur-containing heterocycles. [74][75][76][77][78][79][80][81][82][83][84] Furthermore, most commonly employed protecting groups are compatible with IBX, the use of which in organic synthesis is steadily increasing as a result of these advantages.…”
Section: Simple Oxidation Of Alcohols and Diolsmentioning
confidence: 99%
“…These results suggested that the activity of fumagillin could be optimized further. We additionally described the anti-trypanosomal activity of ovalicin, whose structure closely resembles that of fumagillin, and ovalicin analogues 8. Evidence for a direct interaction of PfMetAP2 with fumagillin was also recently reported 9…”
mentioning
confidence: 89%
“…Intermolecular HR of an aryl iodide [479] (−)-Eptazocine 415 Asymmetric intermolecular HR of an aryl triflate [145] 8.6 Syntheses of Heterocycles, Natural Products, and Other Biologically Active Compounds 615 (continued overleaf ) Asymmetric intramolecular HR of an alkenyl triflate [204] (±)-Ovalicin, C4(S*)-isomer, and its C5-analogs Intramolecular HR of an alkenyl iodide [528] (±)-Oxerine Intramolecular HR of an hetaryl bromide [291] of the freely rotating allyl group in 400 and thereby resulting in an association with the sterically congested trimethylcyclohexene moiety in the molecule. Because the Heck reaction tolerates a variety of functionalities, extensive use of protecting groups is not necessary, and thus, many highly functionalized target molecules can be assembled in just a few highly efficient steps.…”
Section: Natural Product Reaction Type Referencesmentioning
confidence: 99%